Color stability evaluation of micro hybrid composite resins submitted to accelerated artificial aging - Ávila, Gisseli Bertozzi; Dias, Sérgio Candido; Valente, Mariana Lima da Costa; Agnelli, José Augusto Marcondes; Reis, Andréa Cândido dos (Clinical and Laboratorial Research in Dentistry, 2015)
Objective: The aesthetics of dental materials is extremely important for the success of oral rehabilitation. Thus, in the present study we evaluated the color stability and the surface degradation of three micro hybrid composite resins after accelerated artificial aging process (AAA). Methods: Were prepared 24 specimens (n=8) for each material: Solidex, Artglass and Cesead, dimensions of Ø 15 mm by 2 mm in thickness. The samples were subjected to color analysis, before and after AAA, in a spectrophotometer according to the CIE L*a*b* parameters, and a sample of each material, was selected for morphological evaluation under scanning electron microscopy (SEM). The data were submitted to one-way ANOVA and Tukey test (α=0.05). Results: Artglass showed higher stability regarding the presence of red and yellow (p<0.05) when subjected to the AAA and fewer of these pigments (p<0.05) when compared to the Cesead and Solidex, which showed the highest luminance stability (p<0.05). ΔE Cesead was the most unstable (p<0.05). All resins analyzed by SEM showed superficial degradation when submitted to the AAA, mainly in resin Cesead. Conclusion: All materials analyzed demonstrate color change and surface degradation, Cesead resin showed the worse results.